Expression of p53 in epithelial ovarian tumors - Nihad Abdul Razak Amanullah; Usha Poothiode; Letha Vilasiniamma (Wolters Kluwer Medknow Publications, 2020)
Background: Ovarian cancers remain the most lethal of all gynecological malignancies despite major developments in their treatment. Objectives: To study the rate of expression and staining patterns of p53 in various histological types and grades of epithelial ovarian tumors (EOT). Materials and Methods: Sixty EOTs received in a tertiary care center were studied for gross, microscopy, and p53 immunohistochemistry (IHC) expression patterns. Parameters such as age, laterality of tumor, ascites, capsule rupture, tumor size, stage at presentation, metastasis, tumor grade, and number of mitosis were correlated. Results: Of the sixty cases studied, 23 (38.3%) were malignant. Serous carcinomas were the largest group with 17 cases (74%) followed by mucinous with 4 cases (17%) and 2 clear cell carcinomas (9%). All benign and borderline EOT were p53 negative. 65.2% of the malignancies were p53 positive and all of them were serous malignancies. 15 out of 16 high-grade serous carcinomas were p53 positive (94%), while one case was negative (6%). 10 cases (63%) showed intense diffuse positivity of more than 60% of the nucleus, while 5 cases (31%) showed aberrant null staining <5% staining of the nucleus. All mucinous, clear cell carcinomas, and the only low-grade serous carcinoma in the study were p53 negative. P53 staining had positive correlations with variables like capsule rupture, ascites, laterality, and CA 125. Conclusions: The study highlights the different rates of expression and staining patterns of p53 and the need for correct interpretation of p53 IHC for the diagnosis of various EOT.